2017
DOI: 10.1002/jcp.25880
|View full text |Cite
|
Sign up to set email alerts
|

Identification of murine phosphodiesterase 5A isoforms and their functional characterization in HL‐1 cardiac cell line

Abstract: Phosphodiesterase 5A (PDE5A) specifically degrades the ubiquitous second messenger cGMP and experimental and clinical data highlight its important role in cardiac diseases. To address PDE5A role in cardiac physiology, three splice variants of the PDE5A were cloned for the first time from mouse cDNA library (mPde5a1, mPde5a2, and mPde5a3). The predicted amino acidic sequences of the three murine isoforms are different in the N-terminal regulatory domain. mPDE5A isoforms were transfected in HEK293T cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 44 publications
(73 reference statements)
0
43
0
Order By: Relevance
“…However, although all HLA‐G isoforms are presumed to be generated by alternative splicing of a common pre‐mRNA, it remains possible that they could be derived from separate mRNA that are transcribed from distinct and internal promoters. These have been previously reported for several genes such as phosphodiesterase 5A (PDE5A) and TP53 (Campolo et al ., ; Lin et al ., ; Surget et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, although all HLA‐G isoforms are presumed to be generated by alternative splicing of a common pre‐mRNA, it remains possible that they could be derived from separate mRNA that are transcribed from distinct and internal promoters. These have been previously reported for several genes such as phosphodiesterase 5A (PDE5A) and TP53 (Campolo et al ., ; Lin et al ., ; Surget et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The α-signal DNA was synthesized as two short single strands complementary sequences containing at the 5′ and 3′ end the Xba I and Sal I sites (Fwd: ctag atg aat ata ttt tac ata ttt ttg ttt ttg ctg tca ttc gtt caa ggt agg ggt gtg ttt cgt cga g; Rev: tc gac tcg acg aaa cac acc cct acc ttg aac gaa tga cag caa aaa caa aaa tat gta aaa tat att cat), respectively, and then annealed. The 2.6 Kbp Sal I– Sma I PDE5A1 fragment was purified from p3XFLAG-CMV7 [ 36 ]. The two fragments were ligated into the Bluescript KS (Stratagene) plasmid digested with Xba I– Sma I.…”
Section: Methodsmentioning
confidence: 99%
“…pYG137/1 was also used to construct p3XFlagPDE5A1, p3XFlagPDE5A2 and p3XFlagPDE5A3 which contain the M. musculus Pde5a1, a2 and a3 spliced-variants of the Pde5 gene fused at their 5′ end to the short DNA sequence coding for the 3XFLAG peptide (Sigma), an immunogenic peptide for the affinity purification of PDEs from whole cellular extracts. These recombinant vectors were constructed in two stages from pα-PDE5A1 and the p3XFLAG-CMV7 vectors containing either Pde5a1, a2 or a3 in frame with the 3XFLAG coding sequence [ 36 ]. To start, pα-PDE5A1 was digested with Pml I, ligated and transformed in E. coli cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one PDE5 subtype (PDE5A) is alternatively expressed as three isoforms (PDE5A1, PDE5A2, PDE5A3), although dispute persists concerning the physiological relevance of these to cardiac physiology. Whilst some studies have reported either no or minimal cardiac expression of PDE5 [56,[169][170][171], others have detected it within certain cell types [172][173][174]. In isolated cardiomyocytes, PDE5 appears restricted to the cytosol where it is anchored to the Z-lines and preferentially hydrolyses NO/cGMP (although this may change with disease) [92,175,176].…”
Section: Cardiac Physiologymentioning
confidence: 99%